Analysis of Rampant Caries Incidence in Kindergarten School 5 – 6 Years Old Kids and A Factor Affecting it in the Working Area of Kaibon Public Health Center in the Madiun District, 2020 - Pudji Lestari; Siti Farida Noor Layla (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The rampant caries is interacting multifactorial disease occurs very quickly, and concerns multiple teeth, and often cause pain. Conditions of caries in children due to unfamiliarity of parents, against the main cause of dental caries. . Caries in the deciduous tooth caused by exposure of teeth by sweet liquids, in the long term. This study aims to analyze the relationship between mother’s knowledge, mother’s motivation about dental health and consumption patterns of formula milk using a bottle nipples with incidence rampant caries. The research method was analytic observational, with the cross-sectional design. The population of this study are mothers and their children is 538 people. A sampel of 229 people used proportional random sampling technique. Statistic test used is multiple linear regression. The research results show that mother’s knowledge, mother’s motivation, and consumption patterns formula milk using a bottle nipples has a significant relationship both partially and simultaneously the significance level of caries grade was less than 0,05(p<0,05). Regression models that can be formed are y (incidence of rampant caries) = 4,577 – 0,785 mother’s knowledge – 0,345 mother’s motivation + 0,223 comsumption pattern. Increased knowledge and motivation of mothers and decreased consumption patterns of milk using bottles will have an effect on reducing the incidence of rampant caries.